Motor cortical neuronal hyperexcitability associated with α-synuclein aggregation - Liqiang Chen; Hiba Douja Chehade; Hong-Yuan Chu (npj Parkinson's Disease)
Αbstract In Parkinson’s disease (PD), Lewy pathology deposits in the cerebral cortex, but how the pathology disrupts cortical circuit integrity and function remains poorly understood. To begin to address this question, we injected α-synuclein (αSyn) preformed fibrils (PFFs) into the dorsolateral striatum of mice to seed αSyn pathology in the cortical cortex and induce degeneration of midbrain dopaminergic neurons. We reported that αSyn aggregates accumulate in the motor cortex in a layer- and cell-subtype-specific pattern. Specifically, αSyn aggregates-bearing intratelencephalic neurons (ITNs) showed hyperexcitability, increased input resistance, and decreased cell capacitance, which were associated with impaired HCN channel function. Morphologically, the αSyn aggregates-bearing ITNs showed shrinkage of cell bodies and loss of dendritic spines. Last, we showed that partial dopamine depletion is not sufficient to alter thalamocortical transmission to cortical pyramidal neurons. Our results provide a novel mechanistic understanding of cortical circuit dysfunction in PD.